Bridging therapies: ex vivo liver xenoperfusion and the role of machine perfusion: an update - Czigány, Zoltán; Shirini, Kasra; Putri, Aghnia Jolanda; Longchamp, Alban E.; Bhusal, Subarna; Kamberi, Shani; Meier, Raphael P. H. (Xenotransplantation, 2025)
Advancements in xenotransplantation intersecting with modern machine perfusion technology offer promising solutions to patients with liver failure providing a valuable bridge to transplantation and extending graft viability beyond current limitations. Patients facing acute or acute chronic liver failure, post-hepatectomy liver failure, or fulminant hepatic failure often require urgent liver transplants which are severely limited by organ shortage, emphasizing the importance of effective bridging approaches. Machine perfusion is now increasingly used to test and use genetically engineered porcine livers in translational studies, addressing the limitations and costs of non-human primate models. Current reports about artificial and bioartificial liver support combined with xenografts showcase the potential in ex vivo xenogeneic perfusion. Breakthroughs, such as the perfusion of genetically modified porcine liver with FDA-approved machine perfusion systems connected to human blood circulation, underscore the interest and potential feasibility of a “liver dialysis” bridge to allotransplantation or recovery. This review provides an overview of the past and current research in the field of ex vivo pig liver xenoperfusion.